Beneficial Effect of the SGLT2 Inhibitor Empagliflozin on Glucose Homeostasis and Cardiovascular Parameters in the Cohen Rosenthal Diabetic Hypertensive (CRDH) Rat. (July 2018) - Younis, Firas; Leor, Jonathan; Abassi, Zaid; Landa, Natalie; Rath, Lea; Hollander, Kenneth; Naftali-Shani, Nili; Rosenthal, Talma
The effectiveness of empagliflozin (EMPA), a sodium glucose cotransporter type 2 inhibitor, on the kidney, pancreas, and heart was investigated in the Cohen Rosenthal diabetic hypertensive rat model (CRDH rat). Six-week-old CRDH male rats were fed a sugar diet (SD) and treated with the compound EMPA (group Drug/SD) or respective comparator with vehicle (group Veh/SD). A control group was fed a regular diet without treatment (group Veh/P). Preventive treatment with EMPA was measured during 4 months of follow-up. The treatment effect was evaluated according to results observed after 4 months in group Drug/SD when compared to those in group Veh/SD. Significant effect resulted in the following parameters: enhancement of urinary glucose excretion in association with diuresis; amelioration of postprandial hyperglycemia and fasting blood glucose levels; and decrease in calculated Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) as well as lower systolic and diastolic blood pressures. At the end of treatment, EMPA preserved nephrin integrity in the kidney, reduced proteinuria, and prevented diabetes-induced damage to glomerular diaphragm structure. In the pancreas, EMPA demonstrated an impressive decrease in fatty infiltration and atrophy. Blood pressure was significantly reduced in the EMPA-treated group (15 ± 5.1 mm Hg, P < .05) in contrast to the vehicle and control groups. Finally, compared to controls, EMPA significantly reduced left ventricle (LV) mass and LV systolic dilatation, according to 2-dimensional echocardiography. The importance of the study lies in demonstrating the efficacy of an antidiabetic drug with beneficial effects on blood pressure, weight, kidney, and pancreas and a positive effect on the heart.